2017
DOI: 10.1186/s12903-017-0391-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of stress, depression, and suicidal ideation with subjective oral health status and oral functions in Korean adults aged 35 years or more

Abstract: BackgroundOral health greatly affects well-being throughout the different stages of life from childhood to late adulthood. Loss of teeth due to poor oral health hinders mastication, leading to poor nutrition absorption, and affects pronunciation and aesthetics, leading to interpersonal difficulties. As social activities become limited, a sense of isolation and loneliness, stress, and depression grows while happiness decreases. This study aimed to examine the association of stress, depression, and suicidal idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 23 publications
8
32
0
1
Order By: Relevance
“…As was also the case in the study conducted by Kim et al. (2017), in which depression was 2.8 times higher among the women. According to Kessler (2003), although the gender differences begin in puberty, other situations related to sexual hormone changes (pregnancy, menopause, use of oral contraceptives, and use of hormone replacement therapy) did not significantly influence depression.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As was also the case in the study conducted by Kim et al. (2017), in which depression was 2.8 times higher among the women. According to Kessler (2003), although the gender differences begin in puberty, other situations related to sexual hormone changes (pregnancy, menopause, use of oral contraceptives, and use of hormone replacement therapy) did not significantly influence depression.…”
Section: Discussionsupporting
confidence: 75%
“…(2015) 22 who conducted a cross-sectional study with 1,047 persons in the Northeastern region of Thailand, and observed that 39% of the men and 48% of women had light to severe symptoms of depression. As was also the case in the study conducted by Kim et al (2017), 23 in which depression was 2.8 times higher among the women. According to Kessler (2003), 24 although the gender differences begin in puberty, other situations related to sexual hormone changes (pregnancy, menopause, use of oral contraceptives, and use of hormone replacement Oral health and symptoms of depression therapy) did not significantly influence depression.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…With the global aging of the population and increasing life expectancies, the issue of QOL in the elderly population, i.e., how people can remain healthy in later years, has gained great attention [6,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…Not only does reduced saliva secretion lead to increased vulnerability to dental caries and periodontal diseases in the elderly, but it can also result in oral ulcer and erythema, causing severe discomfort when wearing dentures [3,4]. In addition, oral health has a great impact on self-esteem and quality of life (QOL) in the elderly because it affects pronunciation and physical appearance, which are both of vital importance to social life and interpersonal relationships [5,6]. Finally, tooth loss as a result of oral diseases weakens masticatory function and causes oral discomfort while chewing.…”
Section: Introductionmentioning
confidence: 99%